Modeling secondary particle tracks generated by intermediate- and low-energy protons in water with the Low-Energy Particle Track Simulation code. (January 2017) - Verkhovtsev, Alexey; Traore, Ali; Muñoz, Antonio; Blanco, Francisco; García, Gustavo
Abstract: Using a recent extension of the Low-Energy Particle Track Simulation (LEPTS) Monte Carlo code, we model the slowing-down of heavy charged particles propagating in water, combined with an explicit molecular-level description of radiation effects due to the formation of secondary electrons, their propagation through the medium, and electron-induced molecular dissociations. As a case study, we consider the transport of protons with the initial energy of 1 MeV until their thermalization, so that we cover the energy range that contributes mainly to the energy deposition in the Bragg peak region. In order to include protons into the simulation procedure, a comprehensive dataset of integral and differential cross sections of elastic and inelastic scattering of intermediate- and low-energy protons from water molecules is created. Experimental and theoretical cross sections available in the literature are carefully examined, compared and verified. The ionization cross section by protons includes recent experimental measurements of the production of different charged fragments. Abstract : Highlights: Simulation of the full slowing-down of protons in water with LEPTS track-structure code. Explicit molecular-level description of radiation-induced effects. A complete dataset of cross section for scattering of intermediate- and low-energy protons from water molecules is created.